2013
DOI: 10.1016/j.neulet.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cortical activity in response to visually induced postural perturbation: Combined VR and EEG study

Abstract: There is evidence from EEG studies that unexpected perturbations to standing posture induce a differential modulation of cortical activity compared to self-initiated and/or predictable conditions. However, the neural correlates of whole body postural response to visually-induced perturbations on standing posture have not been examined. Here we employ a novel experimental paradigm via combined Virtual Reality (VR) and EEG measures to examine the effects of visually induced perturbations on the dynamics of postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 16 publications
3
33
0
1
Order By: Relevance
“…This interpretation is in agreement with the results of Horak et al ( 1989 ) demonstrating prior experience as well as knowledge of perturbation amplitude reduced the compensatory reaction. Furthermore, anticipation of perturbation onset has been shown to not only induce post-perturbation changes in N1 amplitude, but also adaptations in pre-perturbation cortical and muscular activity (Jacobs et al, 2008 ; Mochizuki et al, 2008 ; Slobounov et al, 2013 ). To exclude that the latter was the case in our study; we have also analyzed EEG and EMG activity prior to perturbation onset for each trial, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is in agreement with the results of Horak et al ( 1989 ) demonstrating prior experience as well as knowledge of perturbation amplitude reduced the compensatory reaction. Furthermore, anticipation of perturbation onset has been shown to not only induce post-perturbation changes in N1 amplitude, but also adaptations in pre-perturbation cortical and muscular activity (Jacobs et al, 2008 ; Mochizuki et al, 2008 ; Slobounov et al, 2013 ). To exclude that the latter was the case in our study; we have also analyzed EEG and EMG activity prior to perturbation onset for each trial, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, similar to its gel-based counterpart, the dry EEG system, with only few electrodes, can index the increase in cognitivemotor effort generated due to a recruitment of neural resources to face an increasing challenge. This increased recruitment may come from frontal and parietal regions, reflecting increased involvement of attentional engagement/working memory and multimodal sensory processing, respectively, while executing a visuomotor task (Gentili et al, 2011;Hatfield, Haufler, Hung, & Spalding, 2004;Jaiswal et al, 2010;Rietschel et al, 2012;Slobounov et al, 2000Slobounov et al, , 2013.…”
Section: Cognitive-motor Effort Assessment Capabilities Of the Dry mentioning
confidence: 99%
“…It is well established that a reduction of alpha (and particularly high-alpha) power would reflect an intensified recruitment of the relevant cognitivemotor resources deployed to perform the task. It was also observed that an increase of task demand resulted in theta synchrony in the frontal region, reflecting recruitment of attentional resources for working memory, action monitoring, and concentration (Cheng et al, 2015;Chuang, Huang, & Hung, 2013;Coombes, Janelle, Duley, & Conway, 2005;Gentili, Bradberry, Oh, Hatfield, & Contreras Vidal, 2011;Gentili et al, 2014;Gevins & Smith, 2000, 2003Gevins et al, 1998;Hsieh & Raganath, 2014;Jaiswal, Ray, & Slobounov, 2010;Klimesch, 1999;Miyata, Tanaka, & Hono, 1990;Rietschel et al, 2012;Slobounov, Fukada, Simon, Rearick, & Ray, 2000;Slobounov, Rearick, Simon, & Johnston, 2000;Slobounov, Teel, & Newell, 2013). Thus, as a whole, these spectral measurements can index the magnitude of recruitment of cognitive-motor resources needed to perform under a given condition of challenge, reflecting the degree of cognitivemotor effort engaged during task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians in sports medicine have tended to be vague about the precise nature of what is referred to as mild traumatic brain injury (mTBI) (McCrory et al, 2013;Slobounov, Teel, & Newell, 2013). Signoretti et al (2010) claim that, "there are still no standard criteria for the diagnosis and treatment for this peculiar condition."…”
Section: How Strong Is the Evidence On Which The Sought For Prohibmentioning
confidence: 99%